2022
DOI: 10.1101/2022.03.24.22272835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relative Effectiveness of Four Doses Compared to Three Dose of the BNT162b2 Vaccine in Israel

Abstract: Objectives: The rapid spread of the Omicron variant (B.1.1.529) alongside evidence of a relatively rapid waning of the third dose prompted Israel to administer a fourth dose of the BNT162b2 vaccine on January 2022. Thus far, sufficient real-world evidence demonstrating the effectiveness of a fourth dose against infection and severe COVID-19 are lacking. This study examined the short-term effectiveness of a fourth dose compared to three doses over the span of 10 weeks. Design: A retrospective test-negative cas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…Recent studies in Israel among adults aged ≄60 years suggest that effectiveness of fourth doses of BNT162b2 against infection may wane faster than third doses, but similar to third doses, there is a lower degree of waning against severe disease. 15,16 Canadian studies have found that immune protection among LTC residents wanes much faster than younger, healthier adults after 2 doses; similar patterns may be expected for booster doses. 28,29…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Recent studies in Israel among adults aged ≄60 years suggest that effectiveness of fourth doses of BNT162b2 against infection may wane faster than third doses, but similar to third doses, there is a lower degree of waning against severe disease. 15,16 Canadian studies have found that immune protection among LTC residents wanes much faster than younger, healthier adults after 2 doses; similar patterns may be expected for booster doses. 28,29…”
Section: Discussionmentioning
confidence: 73%
“…In Israel, among adults aged ≄60 years, the marginal effectiveness against any infection 7-13 days after a fourth dose versus a third dose of BNT162b2 received ≄4 months earlier was 46%, peaking 21-27 days after vaccination at 64%. 16 The marginal effectiveness against severe disease was 73% 7-27 days following a fourth dose and was highest 49-69 days after vaccination at 86%. 16 Similar to our study, there was considerable additional protection against infection and severe disease with a fourth dose relative to a third dose, though findings cannot be directly compared due to differences in study design, outcome definitions, population characteristics, settings, vaccine products, and dosing intervals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, as all monoclonal antibody (mAb) treatments target this same protein, such antigenic shifts not only hamper the protection of vaccines, but can also reduce the efficacy of a wide range of other treatments. Second, multiple studies have shown that vaccines’ protection, including against severe disease, typically wanes within just a few months, after the second 9 , third 10,11 , or the fourth dose 12 . Third, recent lines of evidence in mice and NHP suggest that updated versions of vaccines have diminished efficacy and may be subject to original antigenic sin 13,14 .…”
Section: Introductionmentioning
confidence: 99%